2002
DOI: 10.1007/s00477-002-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphical characterisation of probability distribution tails

Abstract: The purpose of this paper is to present a graphical method to characterise the nature of a distribution (exponential or algebraic). In the algebraic case, this statistical tool provides an estimation procedure of the parameter characterising the decrease of the survival function. The realizations of the random variable under study being available in the form of time series, this method is based on the relationship between the duration of exceeding an intensity threshold and the accumulation of the realizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…The results of this study also converge with other recent studies such as those by Chaouche (2001), Chaouche et al (2002), Coles et al, (2003) and Sisson et al (2003), which all verify the EV2/Pareto behaviour in the tail of the distribution of rainfall extremes and exclude the possibility of EV1/exponential behaviour. In particular, Chaouche (2001) exploited a data base of 200 rainfall series of various time steps (month, day, hour, minute) from the five continents, each including more than 100 years of data.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…The results of this study also converge with other recent studies such as those by Chaouche (2001), Chaouche et al (2002), Coles et al, (2003) and Sisson et al (2003), which all verify the EV2/Pareto behaviour in the tail of the distribution of rainfall extremes and exclude the possibility of EV1/exponential behaviour. In particular, Chaouche (2001) exploited a data base of 200 rainfall series of various time steps (month, day, hour, minute) from the five continents, each including more than 100 years of data.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…Recently, Koutsoyiannis and Baloutsos (2000), Chaouche et al (2002), , , Sisson et al (2006), Koutsoyiannis (2004a, b) and Bacro and Chaouche (2006) have shown that extreme rainfall quantiles can be seriously underestimated by the Gumbel distribution. This discussion has significant practical consequences, particularly for high return periods used for the design of major hydraulic constructions or the estimation of risk of extreme floods.…”
Section: Distribution Of Annual Maximum Rainfallmentioning
confidence: 98%
“…La procédure de calcul des bornes de cet intervalle procède de la délimitation du domaine permis pour le paramètre ξ, conditionnellement à l'échantillon observé (Chaouche & Bacro, 2004a); la statistique qui dérive de cette délimitation, à savoir Ce premier résultat, que nous allons remettre en discussion dans ce qui suit, signifie entre autres que le maximum des cumuls journaliers appartient au domaine d'attraction de Fréchet, c'est-à-dire admet une queue de distribution qui est à décroissance algébrique; ceci rejoint des résultats de travaux menés sous l'égide de P. Hubert (Chaouche et al, 2002) avec une approche non-paramétrique, concernant la caractérisation des queues de distribution de séries pluviométriques ainsi que ceux de Koutsoyiannis (2004a,b).…”
Section: Caracterisation De La Queue De Distribution Des Cumuls Journunclassified